Dinamika Pasar dan Budaya Membaca : Sejarah Populeritas Genre Novel - Yeremias Bardi; Katharina Woli Namang; Yoseph Hendra (Pusat Riset dan Inovasi Nasional, 2024)
This research explores the relationship between the dynamics of the literary market, reading culture, and the development of the popularity of the novel genre. In this study, we discuss how social transformation, innovation in publishing technology, and shifts in reader preferences shaped the novel genre from the 18th century to the modern era. A historical approach and literary analysis are used to highlight the important role of publishers, book distribution, and technology in expanding the reach of novels to a wider audience.